PENERAPAN MODEL PEMBELAJARAN CLASS-WIDE PEER TUTORING (CWPT) DISERTAI MEDIA CERGAM UNTUK MENINGKATKAN KUALITAS PEMBELAJARAN BIOLOGI SISWA KELAS X 7 SMA NEGERI 2 SUKOHARJO TAHUN PELAJARAN 2011/2012 - Hidayah, Evi Noor; Sajidan, Sajidan; Sugiharto, Bowo (Pendidikan Biologi, 2012)
ABSTRACT ? The aim of this research is improve quality of biology learning for teacher?s performance, conditioning class, student science attitude in class, and student motivation of achievement in student class X 7 in 2nd senior high school of Sukoharjo. The research is classroom action research. The steps of research include planning, acting, observing, and reflecting. The collecting data of research uses questionnaire, observation, and interview. Validation data uses triangulation of methods and triangulation of observers. The research uses descriptive as analytic data. The acts of research are consists of three cycles. The result in cycles I describes that generally the research target is not achieve yet that showed teacher?s performance indicators are 86,46%, conditioning class indicators are 62,14%, science attitude of students in class are 62,86%, and motivation of achievement in students are 53,33%. The result in cycles II describes that the research target is not achieve yet optimally that showed teacher?s performance indicators are 100%, conditioning class indicators are 67,86%, science attitude of students in class are 63,81%, and motivation of achievement in students are 65,40%. The result in cycles III describes that the research target is completely achieve and showed that teacher?s performance indicators are 100%, conditioning class indicators are 75,71%, science attitude of students in class are 75,72%, and motivation of achievement in students are 79,05%. Cycles stopped in cycles III because the research target is achieve. The conclusion of this research describes that the implementation of Class-Wide Peer Tutoring learning model with drew story medium can improve quality of biology learning for teacher?s performance, conditioning class, science attitude of student, and motivation of achievement in student of class X 7 in 2nd senior high school of Sukoharjo. Keyword: Class-Wide Peer Tutoring, drew story medium, quality of biology learning